Penerapan Metode Sugeno dalam Menganalisa Gangguan Jiwa Multiple Identity Disorder - Irwan Gulo (Journal of Pharmaceutical and Health Research, 2020)
Multiple identity disorder (previously known as multiple personality disorder) is a mental disorder caused by severe trauma in childhood (3-11 years) and adolescents (12-18 years). Someone can be known that true suffering from multiple identity disorder mental illness, the sufferer must consult a specialist doctor to be diagnosed first. In this case not all sufferers do not have the opportunity to consult a doctor directly because of busyness or expensive consultation fees. One effort that can be done to provide solutions to solving the problem above is to use an application or expert system that can diagnose the mental disorder. In the reasoning process, the Takagi-Sugeno-Kang fuzzy inference system method is used, where fuzzy logic is an appropriate way to map an input space into an output space. In fuzzy logic there are several processes, namely the determination of fuzzy sets, the application of if-then rules and the fuzzy inference process. The system that has been designed can be able to provide optimum diagnostic results in accordance with the results of experts who can help patients to make a diagnosis.